Adhesion proteins--an impact on skeletal myoblast differentiation. - Marta Przewoźniak (Public Library of Science (PLoS), 2013)
Formation of mammalian skeletal muscle myofibers, that takes place during embryogenesis, muscle growth or regeneration, requires precise regulation of myoblast adhesion and fusion. There are few evidences showing that adhesion proteins play important role in both processes. To follow the function of these molecules in myoblast differentiation we analysed integrin alpha3, integrin beta1, ADAM12, CD9, CD81, M-cadherin, and VCAM-1 during muscle regeneration. We showed that increase in the expression of these proteins accompanies myoblast fusion and myotube formation in vivo. We also showed that during myoblast fusion in vitro integrin alpha3 associates with integrin beta1 and ADAM12, and also CD9 and CD81, but not with M-cadherin or VCAM-1. Moreover, we documented that experimental modification in the expression of integrin alpha3 lead to the modification of myoblast fusion in vitro. Underexpression of integrin alpha3 decreased myoblasts' ability to fuse. This phenomenon was not related to the modifications in the expression of other adhesion proteins, i.e. integrin beta1, CD9, CD81, ADAM12, M-cadherin, or VCAM-1. Apparently, aberrant expression only of one partner of multiprotein adhesion complexes necessary for myoblast fusion, in this case integrin alpha3, prevents its proper function. Summarizing, we demonstrated the importance of analysed adhesion proteins in myoblast fusion both in vivo and in vitro.